Application of Biophysical Techniques to Investigate the Interaction of Antimicrobial Peptides With Bacterial Cells - Gelmi, Maria Luisa; D'Andrea, Luca Domenico; Romanelli, Alessandra (Frontiers in Medical Technology, 2020)
The comprehension of the mechanism of action of antimicrobial peptides is the ground for the design of new and more efficient antibiotics. To this aim it is important to detect modifications occurring to both the peptide and the bacterial cell upon interaction; this will help understanding the peptide structural requirement, if any, at the base of the interaction and also the pathways triggered by peptides ending in cell death. A still limited number of papers describes the interaction of peptides with bacterial cells, while most of the studies published today is focused on model membrane-peptides interactions. Investigations carried out with entire bacterial cells highlighted the limitations connected to the use of oversimplified model membranes and , more importantly, helped to identify molecular targets of antimicrobial peptides and changes occurring to the bacterial membrane. In this review the details on the mechanism of action of antimicrobial peptides, as determined by the application of spectroscopic techniques, as well as scattering, microscopy and calorimetry techniques to complex systems such as peptide/bacteria mixtures are discussed.